Lifestyle, Cardiometabolic and Inflammatory markers in Schoolchildren and their Associations with Body Mass Index: Lifestyle, inflammation markers and Children BMI - Ghomari, Lamia; Ghomari-Boukhatem, Hanane; Raiah, Mourad; Boukhari, Youcef; Bouchenak, Malika (Progress in Nutrition, 2022)
Background: Unhealthy lifestyle behaviors are key elements for weight gain, leading to several chronic diseases. The aim of this study was to evaluate lifestyle, cardiometabolic and inflammation markers and their associations with body mass index (BMI) in children. Methods: Schoolchildren (n = 225; G/B = 109/116); aged 7–10 years were recruited. Waist circumference (WC), and BMI were determined. Daily energy intake (DEI), total energy expenditure (TEE), energy balance (EB), physical activity level (PAL), and quality diet using KidMed index were evaluated. Cardiometabolic and inflammatory markers were estimated. Results: Anthropometric classification showed that 62% of children were normal weight (NW), 19% overweight (OW), 9% obese (O), and 10% thin (T). Compared to NW, OW and O presented respectively higher WC (p<0.05; p<0.01), weight, DEI and EB (p<0.01; p<0.001), and lower PAL (p<0.01 ; p<0.001), TEE and KidMed score (p<0.05 ; p<0.01), while T presented lower weight, DEI, EB and KidMed score (p<0.05). Uric acid (UA) values were higher (p<0.05) in O, leptin, interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) concentrations were higher (p<0.001), and adiponectin levels were lower (p<0.01), in both OW and O, whereas, leptin and TNF-α values were lower, and IL-6 levels were higher (p<0.001) in T. Significant associations between WC, DEI, KidMed, leptin, adiponectin, IL-6, TNF-α and BMI were observed. Conclusion: In response to unhealthy diet, excess energy intake, and sedentary; excessive fat mass is noted inducing inflammatory status in children. These findings highlight the necessity of oriented strategies to track obesity and related diseases.